2014
DOI: 10.1186/1477-7819-12-289
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 positive breast cancer is associated with an increased risk of positive cavity margins after initial lumpectomy

Abstract: BackgroundThe effect of breast cancer subtype on margin status after lumpectomy remains unclear. This study aims to determine whether approximated breast cancer subtype is associated with positive margins after lumpectomy, which could be used to determine if there is an increased risk of developing local recurrence (LR) following breast-conserving surgery.MethodsWe studied 1,032 consecutive patients with invasive cancer who received lumpectomies and cavity margin (CM) assessments from January 2003 to November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
2
17
1
Order By: Relevance
“…The Chinese study by Jia reported the increased likelihood of positive margins among patients with Her-2 positive invasive tumors undergoing breast conserving surgery (Jia et al, 2014). We were not able to establish an association between the positive margin rates and the Her-2 copy number or either the ER or PR receptor status.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The Chinese study by Jia reported the increased likelihood of positive margins among patients with Her-2 positive invasive tumors undergoing breast conserving surgery (Jia et al, 2014). We were not able to establish an association between the positive margin rates and the Her-2 copy number or either the ER or PR receptor status.…”
Section: Discussioncontrasting
confidence: 43%
“…A recent Chinese report indicated that patients with Her-2 positive breast cancer had an increased risk of positive margins following breast conserving surgery (Jia H et al, 2014). We wished to see if Her-2 status was similarly associated with positive margins among our patients.…”
mentioning
confidence: 99%
“…Moreover, the correlation between biological subtypes of breast cancer and involved margins in CSM has been poorly investigated. 9 Our aim was to assess the capability of CSM to reduce positive margin rates and reoperations compared to simple lumpectomy (SL) in a large cohort of breast cancer patients treated in a single center. Secondary aims were to provide a cost analysis between CSM and SL, and to investigate if CSM impacted differently on different biological subtypes of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 1,032 patients from China, of whom 209 had positive margins, reported by Jia, demonstrated that patients with Her-2 positive invasive breast cancers were more likely to have positive margins than patients with Her-2 negative tumors (Jia et al, 2014). Her-2 status was not evaluated in our study.…”
Section: Discussionmentioning
confidence: 83%